2017
DOI: 10.1016/j.cell.2017.02.030
|View full text |Cite
|
Sign up to set email alerts
|

The Upsides and Downsides of Organelle Interconnectivity

Abstract: Interconnectivity and feedback control are hallmarks of biological systems. This includes communication between organelles, which allows them to function and adapt to changing cellular environments. While the specific mechanisms for all communications remain opaque, unraveling the wiring of organelle networks is critical to understand how biological systems are built and why they might collapse, as occurs in aging. A comprehensive understanding of all the routes involved in inter-organelle communication is sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 104 publications
(144 reference statements)
0
82
0
Order By: Relevance
“…Although this strategy provides important structural and functional benefits, specialized functions of the organelles must be coordinated and integrated for cell physiology (Gottschling and Nyström, 2017). Studies have shown that different organelles interact directly and extensively through mechanisms such as membrane contact (Prinz, 2014) and membrane fusion (Martens and McMahon, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although this strategy provides important structural and functional benefits, specialized functions of the organelles must be coordinated and integrated for cell physiology (Gottschling and Nyström, 2017). Studies have shown that different organelles interact directly and extensively through mechanisms such as membrane contact (Prinz, 2014) and membrane fusion (Martens and McMahon, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…During ERAD, misfolded protein substrates are recognized by molecular chaperones such as Hsp70 and ubiquitinated by E3 ubiquitin ligases that are ER associated (2,4). After the acquisition of a polyubiquitin tag, the ERAD substrate is retrotranslocated from the ER in an ATP-dependent process that utilizes the AAA-ATPase, Cdc48 (in yeast) or p97 (in mammals).…”
Section: Identification Of a Romk Variant Suitable Formentioning
confidence: 99%
“…_______________________________________ Protein quality control allows cells in all organisms to survive proteotoxic stresses and fine-tune their proteome in response to environmental changes (1). Significant recent work has elucidated in great detail how protein quality control pathways operate in the cytoplasm and in the endoplasmic reticulum (ER) (2)(3)(4). Common to both pathways is the delivery of substrates to the cytoplasmic proteasome, which selectively degrades ubiquitinated and misfolded protein substrates (5).…”
mentioning
confidence: 99%
“…Such dynamic responses require a highly coordinated network of processes and signals that are largely compartmentalized to specific organelles and subcellular complexes. To orchestrate the vastly complex cellular system, communication between organelles is paramount . Mitochondria act as a cellular hub that senses and integrates environmental changes, and as a coordinator of adaptive responses through constant communication with other cellular compartments, including the nucleus, regulate key cellular processes that have a significant impact on health span and life span .…”
Section: How Do Mitochondria Communicate?mentioning
confidence: 99%